Ethics in qualitative research : controversies and contexts - Hammersley, Martyn; Traianou, Anna (London : SAGE, 2016)
This volume explores the field of research ethics and presents a distinctive perspective; one that is at odds with the assumptions underpinning ethical regulation, but also with the views of many qualitative researchers today.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2016).
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Moral and ethical aspects; Qualitative research -- Moral and ethical aspects